Cellular Level In-silico Modeling of Blood Rheology with An Improved Material Model for Red Blood Cells - Závodszky, Gábor; van Rooij, Britt; Azizi, Victor; Hoekstra, Alfons (Frontiers in Physiology, 2017)
Many of the intriguing properties of blood originate from its cellular nature. Therefore, accurate modelling of blood flow related phenomena requires a description of the dynamics at the level of individual cells. This, however, presents several computational challenges that can only be addressed by high performance computing. We present Hemocell, a parallel computing framework which implements validated mechanical models for red blood cells and is capable of reproducing the emergent transport characteristics of such a complex cellular system. It is computationally capable of handling large domain sizes, thus it is able to bridge the cell-based micro-scale and macroscopic domains. We introduce a new material model for resolving the mechanical responses of red blood cell membranes under various flow conditions and compare it with a well established model. Our new constitutive model has similar accuracy under relaxed flow conditions, however, it performs better for shear rates over 1500 1/s. We also introduce a new method to generate randomised initial conditions for dense mixtures of different cell types free of initial positioning artefacts.